WINE TOURISM: CONSUMER BEHAVIOUR (Development Service Industry Management, 2025)
This article investigates consumer behaviour in the sphere of wine tourism in Ukraine, drawing on an anonymous online survey conducted among 259 respondents representing both wine tourists and ordinary travellers. By differentiating these groups, the study identifies key motivational factors, preferences, and attitudes towards domestic wine products. The findings reveal that wine tourists demonstrate greater loyalty to Ukrainian wines, lower xenocentric biases, and a stronger willingness to experiment with new brands, while ordinary travellers tend to rely more on brand recognition and price sensitivity. The research highlights the role of income level in shaping participation in wine-related events, with higher-income respondents more actively involved in wine tourism activities. Word-of-mouth marketing emerged as a decisive factor across both groups, although wine tourists complemented personal recommendations with professional sources and prior experience.Special attention is devoted to the behaviour of Generation Z, whose members display price sensitivity, growing interest in alternative beverages, and a gradual integration into the culture of wine tourism. The study also uncovers intergenerational differences in the use of digital communication: millennials and zoomers dominate in Instagram activity, whereas Generation X and baby boomers remain more active on Facebook. These findings underline the necessity of differentiated marketing strategies. Moreover, the analysis confirms that emotional impressions gained during wine events are closely aligned with rational evaluations of organisation, service quality, and value-for-money, demonstrating the dual emotional and economic significance of wine tourism. The research contributes to filling the gap in empirical studies of consumer behaviour in Ukrainian wine tourism and offers practical recommendations for the development of targeted marketing approaches, audience segmentation, and promotion strategies. It also emphasises the potential of wine tourism as a cultural and economic phenomenon that fosters regional development and enhances the international recognition of Ukrainian wine.
Keywords: Ukraine; wine tourism; enotourism; consumer; tourist; behavior